Aesthetic in the Poetry of Sayed Sijaz Shah Rashidi - Shahati, Shafique Ahmed; Rashid, Abdul Qudus Hassan (sourcecoder, 2024)
Sayed peer mahay Muneer Hazrat muhi u din shah s/o Hazrat shah was born in 1929 A.D. At his native village Matyari. He was died in 1998 A.D. He was the follower of the Shah Mardan shah Rashdi in Qadri concatenation. He loves to engage with poetry. However, Peer jhando at Saeed Abad Ihsan u Allah (sunhat dhani) was born in 1929 A.D. At his native village، Peer jhando at Saeed Abad Matyari. He was died in 1998 A.D. He was the follower of the Shah Mardan shah Rashdi in Qadri concatenation. He loves to engage with poetry. However, he has written a lot of poetry, His poetry collection “Sukhan e Aijaz” was published in 2003.in additition to other qualities, his poetry also possesses aesthetic appeal. In this article, the analysis of aesthetics in his poetry has been conducted.